IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT THROUGH DEMONSTRATION METHOD AT THE SEVENTH YEAR STUDENTS OF MTsN 1 PARE IN ACADEMIC YEAR 2016/2017 - lestari, Dwi puji (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
S ome difficulties during in learning English are possible happened and mostly English students have difficulties in spoken language. When the researcher taught in VII B, she found some difficulties in speaking especially in descriptive text so the researcher decided to do this study to improve the students’ speaking achievement by using demonstration method whether it can improve students’ achievement of the Seventh year students of MTsN Pare 1.The design of study is classroom action research (CAR). The subject of this research is class VII-B of MTs Negeri 1 Pare. Total numbers of students in VII-B is 35 students. To know the result of students’ activity the researcher used observation checklist, field note, and questionnaire. Meanwhile, to know the improvement of the achievement the researcher used test and observed the result of test by computing the mean and the percentage of classroom success. The result of the study showed that more than 85% students were more active and interest in speaking activity. Based on the result of students’ speaking achievement after being implemented demonstration method is improved, because in cycle 1 was 71.43% of subject who classified into a success with the average was 81.5 and in cycle 2 was 88,57% of subject who classified into a success with the average was 87.09.